PENGELOLAAN ARSIP DINAMIS PADA FAKULTAS USHULUDDIN ADAB DAN DAKWAH (FUAD) IAIN BATUSANGKAR - Manita, Rika Jufriazia (Alfuad: Jurnal Sosial Keagamaan, 2020)
The management of dynamic records becomes the reference of an organization to achieve the goals of the organization. Dynamic archives will not be separated from correspondence in each unit at the agency. The background of this research is that the archives of Ushuluddin Adab and Da'wah (FUAD) IAIN Batusangkar have not been maximized. The research that the author uses is descriptive research with a qualitative approach. There were 4 informants in this assessment consisting of 1 Head of Administration and 4 archiving officers in the Faculty environment, are a receptionist manager, 3 departmental employees namely 1 Department of Library and Islamic Science Department 1 employee, Islamic Broadcast Communication 1 people and employees majoring in Islamic Political Thought 1 person. Based on observations made by the author, it can be concluded that the management of dynamic archives at the Faculty of Usuluddin Adab and Da'wah (FUAD) of Batusangkar IAIN has not run optimally, for the management of incoming and outgoing letters such as official letters, student letters in their distribution require a long time especially when the receptionist was not in place because the receptionist was a lecturer employed. Staff limitations and the difficulty in re-finding archives are due to the management of archives that are not in accordance with the standards and inadequate supporting facilities. Archival shrinkage in the Faculty of Usuluddin Adab and Da'wah has not used the Archive Retention Schedule.